MELK is an oncogenic kinase essential for metastasis, mitotic progression, and programmed death in lung carcinoma - Tang, Qin (Signal Transduct Target Ther, 2020)
Lung cancer is the fastest growth rate of morbidity and mortality in nearly a decade, and remains difficult to treat. Furthermore, the molecular mechanisms underlying its development are still unclear. In this study, bioinformatics analysis showed that MELK was highly expressed in lung cancer and negatively correlated to the survival of lung adenocarcinoma (LUAD). Immunohistochemistry analysis of LUAD patient tissues revealed there were a high level of MELK expression in LUAD. Knockdown of MELK expression inhibits the migration and invasion of LUAD cells, which may be mediated by Twist1, Slug, MMP7, and N-catenin. Overexpression of MELK promoted the growth of LUAD cells in medium, 3D Matrigel, and nude mice. Inhibition of MELK by OTSSP167 arrested cycle of LUAD cells at G2/M phase via PLK1-CDC25C-CDK1 pathway, and triggered apoptosis-mediated pyroptosis. Together, these data indicate that MELK is critical for metastasis, mitotic progression, and programmed death of LUAD and may be a promising therapeutic target for LUAD.